Characteristics of the course acute thromboembolism of the pulmonary artery in women - Tseluyko, Vira; Kharchenko, Liubov (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. According to modern ideas, men have a more unfavorable course during the hospital period of pulmonary embolism. However, in recent years, works have appeared that have conflicting results regarding the influence of gender differences on mortality in pulmonary embolism, including publications in which a more severe course is observed for women. Aim of the research: determination of gender characteristics of the course of acute pulmonary embolism in women compared to men. Materials and methods. 243 patients with acute pulmonary embolism were examined. All patients underwent a physical examination, clinical and biochemical blood tests, assessed the risk and prognosis according to generally accepted scales, performed an electrocardiographic and X-ray examination, a standard transthoracic echocardiography, an ultrasound Doppler examination of the veins of the lower extremities, and a multispiral computed tomographic angiography of the pulmonary arteries. Statistical processing also included multivariate regression analysis. Results. According to the results of the study, it was found that the average age of women who were hospitalized with acute pulmonary embolism is four years older than that of men. In women, such risk factors for the occurrence of venous thromboembolism as: advanced age, history of venous thromboembolism, diabetes mellitus, and oncological disease were more likely to occur. Heart rate and cholesterol levels at admission were also likely to be higher in women than in men. Prediction of the severity of the course of pulmonary embolism determined by the sPESI scale index showed that high risk occurs probably more often in women. The mortality rate in the female group was also relatively higher than that of the male group. Conclusion. It was established that, despite similar lesions of the pulmonary arteries (localization, distribution and volume), there are gender differences in the prevalence of the leading risk factors for pulmonary embolism. It was found that women have a more severe course of acute pulmonary embolism, which is evidenced by a higher specific weight of high-risk patients, more pronounced saturation disturbances and a higher heart rate. In-hospital mortality in women with pulmonary embolism is higher than in men, both in the group as a whole and among high-risk patients.